Low-level laser irradiation modulates the proliferation and the osteogenic differentiation of bone marrow mesenchymal stem cells under healthy and inflammatory condition - Wang, Liying; Wu, Fan; Liu, Chen; Song, Yang; Guo, Jiawen; Yang, Yanwei; Qiu, Yinong (Lasers in medical science, 2019)
The aim of this in vitro study was to evaluate the effects of low-level laser therapy (LLLT) at different energy intensities on proliferation and osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) under healthy and inflammatory microenvironments. Human BMSCs and BMSCs from inflammatory conditions (i-BMSCs, BMSCs treated with tumor necrosis factor α; TNF-α) were subject to LLLT (Nd:YAG;1064 nm) at different intensities. We designed one control group (without irradiation) and four testing groups (irradiation at 2, 4, 8, and 16 J/cm 2 ) for both BMSCs and i-BMSCs. Cell proliferation was measured using colony-forming unit fibroblast assay and 3-(4,5-dimethylthiazol-2yl)-2,5-diphenyltetrazolium bromide assay. Osteogenic capacity of cells was determined by alkaline phosphatase (ALP) staining, ALP activity assay, Alizarin Red S staining and the mRNA transcript levels of genes runt-related transcription factor 2 (Runx2), ALP, and osteocalcin. Moreover, the effects of LLLT on secretion of TNF-α in BMSCs and i-BMSCs were measured by enzyme-linked immunosorbent assay. Our results demonstrated LLLT could significantly promote BMSC proliferation and osteogenesis at densities of 2 and 4 J/cm 2 . LLLT at density of 8 J/cm 2 could promote the proliferation and osteogenesis of i-BMSCs. However, LLLT at 16 J/cm 2 significantly suppressed the proliferation and osteogenesis of BMSCs both in healthy and in inflammatory microenvironment. Moreover, we also found that the expression of TNF-α was obviously inhibited by LLLT at 4, 8, and 16 J/cm 2 , in an inflammatory microenvironment. Considering these findings, LLLT could improve current in vitro methods of differentiating BMSCs under healthy and inflammatory microenvironments prior to transplantation.